Forest Tent Caterpillar, Malacosoma disstria Hübner (Insecta: Lepidoptera: Lasiocampidae) - James R. Meeker (EDIS, 2004)
The forest tent caterpillar, Malacosoma disstria Hübner, is the most widely distributed indigenous tent caterpillar in North America (Furniss and Carolin 1977). The forest tent caterpillar has been recognized as an important defoliator of a wide variety of deciduous hardwood trees throughout its range for many years (Batzer and Morris 1978). Although this univoltine insect is called a tent caterpillar, it is unlike other Malacosoma species in that the larvae do not construct tents. Instead, forest tent caterpillars spin silken mats on the trunks and large branches where they congregate to molt or rest from feeding. Larvae also deposit silk in strands along which they travel to and from feeding sites. The caterpillars themselves are relatively harmless to people (i.e., they do not bite or sting) although a few people have an allergic reaction to handling them. This document is EENY-184 (originally published as DPI Entomology Circular 385), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2001.